Structural-semantic features of derivative in Gregory Lischenyuk's poetry (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article deals with Gregory Lischenyuk’s poetry in the derivation aspect. It defines derivational structure of derivative nouns, fixed in the studied poems; establishes the peculiarities of the semantics of derivatives which have been formed with a help of suffix, confix, prefix, without affix as well as by stem composition and morphological and syntactic way (substantivation). The Productivity of word-formation types and the potency of morphemes are displayed in the description of the eighteen suffixes, affixes, as well as lexical and word-building groups of studied derivatives. Suffixes -к-, -ин(а), -ість showed high productivity, seven formants (-нн(я), -ець, -ок, -от(а), -ств(о), -иц(я), -ик) – average productivity and eight affixes (-чик, -ар, -ц-, -очк-, -ичк-, -ечк-, -ив(о), -тель) were less productive. Comprehensive analysis of the factual material allowed to identify: derived words with the suffix -к-; derivatives with formant -ин(а); word-formation type with the suffix ‑ість; derivatives with suffixes -нн(я) and -ець; nouns with affixes -ок and -от(а); with formants -ств(о), -иц(я), -ик; linguistic units with suffixes -чик, -ар, -ц-, -очк- in the word- formative structure; derived words with formants -ичк-, -ечк-, -ив(о), -тель.The derived words, formed with a help of confix, are functional. They have an interesting and diverse semantics and word-formation structure. Confix structures are presented by nouns which are formed with a help of confix formants.
Keywords: word-formation type; word-formation structure; semantics; derivative